Cardiovascular abnormalities in children with Turner syndrome: a 15-year retrospective study and analysis of warning signs - Jia, Hongliang; Li, Ye; Huang, Panwang; Zeng, Beilei; Zhou, Yuan; Xu, Zhuangjian; Ma, Yaping (Frontiers in Pediatrics, 2025)
Background/ObjectiveThere are limited studies on cardiovascular abnormalities (CAs) and their warning signs in children with Turner syndrome (TS). The main aim of this 15-year retrospective study was to investigate the warning signs of CAs in children with TS and to suggest ways to prevent them.MethodsThis retrospective study analyzed children diagnosed with TS at our pediatric endocrinology clinic. The study examined patients with TS with CAs and their warning signs.ResultsA total of 37 cases were included in our study. The average age at presentation was 7.48 ± 3.49 years. According to the results of transthoracic echocardiography, the children were divided into two groups: (1) TS without CAs (n = 31) and (2) TS with CAs (n = 6). The incidence rate of CAs was 16.2% (6/37). Of the six cases, five had congenital heart disease, four of which underwent cardiac surgery. One patient developed descending aortic coarctation during growth hormone therapy and underwent aortic coarctation repair surgery. The proportions of haplotypes, chimeric types, and structural abnormalities in the TS without CAs group were 9/31, 16/31, and 6/31, respectively. In the TS with CAs group, these proportions were as follows: 1/6, 3/6, and 2/6, respectively. A comparative analysis revealed no statistically significant variation in karyotype frequencies between the two groups. In the TS without CAs group, 0.0% of the mothers had abnormal blood pressure during pregnancy. In the TS with CAs group, the incidence of hypertension in the mothers during pregnancy was 33.3%. A significant difference in gestational hypertension was observed between the two groups (P = 0.016). However, no significant differences were observed between the groups in terms of heart rate or blood pressure parameters (systolic/diastolic).ConclusionsChildren with TS born to mothers with gestational hypertension appear to have a higher prevalence of CAs. These findings suggest that maternal gestational hypertension may serve as a potential early clinical marker for increased cardiovascular risk in this population and may warrant closer postnatal cardiac surveillance.